Effect of stellate ganglion block on uremic restless legs syndrome - ZHANG Ning*，XIE Qipeng，ZHANG Weiwei，FENG Miaomiao，WANG Yunchang，ZHOU Tianyu (Zhongguo linchuang yanjiu)
Objective To observe the effect of stellate ganglion block（SGB）on restless legs syndrome（RLS）and sleep quality in hemodialysis patients. Methods A total of 62 patients with end-stage renal disease complicated with RLS who received regular hemodialysis in Shanxi Bethune Hospital from February 2022 to April 2024 were randomly divided into SGB group（group S）and placebo control group（group C）, and finally 57 patients were included, 29 in group S and 28in group C. Group S received four consecutive SGBs, while group C received 4 consecutive injections of normal saline into the anterolateral muscle tissue of the anterior tubercle of the transverse process at the same level cervical vertebra, all of which were alternately performed bilaterally, and 4 injections were completed within 1 week（every other day）. The International RLS Study Group Rating Scale（IRLS）score and the Pittsburgh Sleep Quality Index（PSQI）score were recorded before treatment, 4, 8 and 12 weeks after treatment, respectively, and the Clinical Global Impression ⁃Improvement Scale（CGI-I）score was recorded 12 weeks after treatment to evaluate the apparent efficiency and record adverse reactions. Results There was no significant difference in IRLS scores and PSQI scores between the two groups before treatment（P＞0.05）. At 4, 8 and 12 weeks after treatment, the IRLS scores and PSQI scores of group S were lower than those before treatment, and were also lower than those in group C during the same period, with statistically significant difference（P<0.01）. At 12 weeks after treatment, the response rate of CGI-I in group S was significantly higher than that in group C（75.86% vs 10.71%, χ2=24.560, P<0.01）. There were no adverse reactions such as puncture site infection, hematoma, nerve injury, and local anesthetic poisoning in the two groups. Conclusion SGB can improve RLS and the sleep quality of uremic patients with good clinical efficacy and high safety.